Karakteristik Penginapan Kampung Wisata Arborek Kabupaten Raja Ampat Provinsi Papua Barat - Anastasia Gustiarini Gustiarini (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2022)
Arborek Village is one of the villages in the Meos Mansar District, Raja Ampat Regency. This village was appointedthe Best Tourism Village in 2015. accommodationservicesare very important to be studied in order to get the right formulation for the development of accommodation in this district. Research held three months, from 1st July until 1st October 2021, technique data collection are observation, interviews, and literature study. The results are presented in the form of a description or descriptive. The results of the research from ten lodgement in Arborek Village have almost the same characteristics, ranging from building materials to the location of the accomodation arrangement, the lodgement has not fully implemented the concept of ecotourism towards development and sustainable (sustainable tourism) especially the ecological pillar because there is no waste management -plastic waste that cannot be recycled but this plastic waste is burned so that it can cause pollution. The potential for accomodation development in implementing the ecotourism concept enough positive, in the future further research is needed related to the carrying capacity of the development of environmentally friendly lodging in Arborek Village.